Pachystachys lutea Golden Shrimp Plant: FPS452/FP452, 6/2007 - Gilman, Edward; Meerow, Alan W. (EDIS, 2007)
This document provides a comprehensive overview of the golden shrimp plant (Pachystachys lutea), a tropical shrub known for its bright yellow bracts and white flowers. It details the plant’s characteristics, including its height, spread, leaf arrangement, and flowering habits. The document also covers the plant’s growing requirements, such as light, soil, and temperature preferences, and offers guidance on propagation and maintenance. Additionally, it highlights the plant’s uses in landscaping and its susceptibility to pests like scales and spider mites. Original publication date October 1999.